The impact of phosphodiesterase inhibition on neurobehavioral outcomes in preclinical models of traumatic and non-traumatic spinal cord injury: a systematic review - Butler, Max B.; Vellaiyappan, Sundar K.; Bhatti, Faheem; Syed, Fazal-E-Momin; Rafati Fard, Amir; Teh, Jye Quan; Grodzinski, Ben; Akhbari, Melika; Adeeko, Sylva; Dilworth, Rory; Bhatti, Aniqah; Waheed, Unaiza; et al. (Frontiers in Medicine, 2023)
The objective of this study is to evaluate the impact of phosphodiesterase (PDE) inhibitors on neurobehavioral outcomes in preclinical models of traumatic and nontraumatic spinal cord injury (SCI).A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines and was registered with PROSPERO (CRD42019150639). Searches were performed in MEDLINE and Embase. Studies were included if they evaluated the impact of PDE inhibitors on neurobehavioral outcomes in preclinical models of traumatic or nontraumatic SCI. Data were extracted from relevant studies, including sample characteristics, injury model, and neurobehavioral assessment and outcomes.Risk of bias was assessed using the SYRCLE checklist.The search yielded a total of 1679 studies, of which 22 met inclusion criteria. Sample sizes ranged from 11 to 144 animals. PDE inhibitors used include rolipram (n = 16), cilostazol (n = 4), roflumilast (n=1) and PDE4-I (n = 1). The injury models used were traumatic SCI (n = 18), spinal cord ischaemia (n = 3), and degenerative cervical myelopathy (n = 1). The most commonly assessed outcome measures were Basso, Beattie, Bresnahan (BBB) locomotor score (n = 13) and grid walking (n = 7). Of the 22 papers that met the final inclusion criteria, 12 showed a significant improvement in neurobehavioral outcomes following the use of PDE inhibitors, 4 papers had mixed findings and 6 found PDE inhibitors to be ineffective in improving neurobehavioral recovery following an SCI. Notably, these findings were broadly consistent across different PDE inhibitors and spinal cord injury models.In preclinical models of traumatic and nontraumatic SCI, the administration of PDE inhibitors appeared to be associated with statistically significant improvements in neurobehavioral outcomes in a majority of included studies. However, evidence was inconsistent with a high risk of bias. This review provides a foundation to aid interpretation of subsequent clinical trials of PDE inhibitors in spinal cord injury.